Prognostic significance of tumor-infiltrating lymphocytes in ductal carcinoma in situ of the breast - Toss, Michael S.; Miligy, Islam; Al-Kawaz, Abdubaqi; Alsleem, Mansour; Khout, Hazem; Rida, Padmashree C.; Aneja, Ritu; Green, Andrew R.; Ellis, Ian O.; Rakha, Emad (Nature Publishing Group, 2018)
Tumor-infiltrating lymphocytes (TILs) provide prognostic value in invasive breast cancer and guidelines for their assessment have been published. This study aims to evaluate: (a) methods of TILs assessment, and (b) their prognostic significance in breast ductal carcinoma in situ (DCIS). Hematoxylin and eosin sections from two clinically annotated DCIS cohorts; a training set (n = 150 pure DCIS) and a validation set (n = 666 comprising 534 pure DCIS and 132 cases wherein DCIS and invasive breast carcinoma were co-existent) were assessed. Seven different scoring methods were applied to the training set to identify the most optimal reproducible method associated with strongest prognostic value. Among different methods, TILs touching ducts' basement membrane or away from it by one lymphocyte cell thickness provided the strongest significant association with outcome and highest concordance rate [inter-cluster correlation coefficient = 0.95]. Assessment of periductal TILs at increasing distances from DCIS (0.2 , 0.5 , and 1 mm) as well as percent of stromal TILs were practically challenging and showed lower concordance rates than touching TILs. TILs hotspots and lymphoid follicles did not show prognostic significance. Within the pure DCIS validation set, dense TILs were associated with younger age, symptomatic presentation, larger size, higher nuclear grade, comedo necrosis and estrogen receptor negativity as well as shorter recurrence-free interval (p = 0.002). In multivariate survival analysis, dense TILs were independent predictor of shorter recurrence-free interval (p = 0.002) in patients treated with breast conservation. DCIS associated with invasive carcinoma showed denser TILs than pure DCIS (p = 9.0 × 10-13). Dense TILs is an independent prognostic variable in DCIS. Touching TILs provides a reproducible method for their assessment that can potentially be used to guide management.